Association of Serum Inflammatory Biomarkers (CRP, IL-6, TNF-α) with Ocular Complications and Severity of Chronic Rhinosinusitis in Diabetic and Non-Diabetic Patients - S M Qsisar Sajjad, Sohaib Farooq Multan, Abdur Rauf Hammad, Ahsan Qureshi, Muhammad Yousuf Memon, Aisha Aziz (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Chronic rhinosinusitis (CRS) is a long-standing inflammatory condition of the nasal and paranasal sinuses that often leads to significant morbidity. In patients with diabetes mellitus, impaired immunity and a persistent pro-inflammatory state aggravate the disease, increasing its severity and the risk of complications such as ocular involvement. Circulating inflammatory biomarkers including C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) play a vital role in the inflammatory response and may reflect the extent of CRS and its related complications. Objective: To determine the association between serum levels of CRP, IL-6, and TNF-α with the severity of chronic rhinosinusitis and the occurrence of ocular complications in diabetic and non-diabetic patients. Methods: This cross-sectional analytical study was conducted at the Multan Medical and Dental College, Multan and Sir Syed College of Medical Sciences for Girls, Karachi, Pakistan, from May 2022 to May 2023. A total of 130 patients diagnosed with CRS were included and divided into two groups: diabetics (n = 65) and non-diabetics (n = 65). Diagnosis was based on EPOS 2020 criteria, and disease severity was assessed using the Lund–Mackay CT scoring system. Serum CRP, IL- 6, and TNF-α levels were measured using ELISA, and findings were correlated with CRS severity and ocular complications. Statistical analysis was performed using SPSS version 26, and a p-value < 0.05 was considered significant. Results: The mean levels of CRP, IL-6, and TNF-α were significantly higher in diabetic CRS patients (10.4 ± 2.9 mg/L, 42.3 ± 9.7 pg/mL, and 35.7 ± 8.1 pg/mL, respectively) compared to non-diabetics (6.1 ± 1.8 mg/L, 26.5 ± 8.2 pg/mL, and 21.2 ± 7.4 pg/mL; p < 0.001). The mean Lund–Mackay score was also higher among diabetics (14.2 ± 3.9) than non-diabetics (9.3 ± 3.1; p < 0.001). Ocular complications were more common in diabetic CRS patients (40%) than in non-diabetic patients (12.3%), with orbital cellulitis and dacryocystitis being the most frequent findings. Significant positive correlations were found between biomarker levels and CRS severity (CRP r = 0.68; IL-6 r = 0.74; TNF-α r = 0.71; p < 0.001). Conclusion: Elevated serum levels of CRP, IL-6, and TNF-α are strongly associated with increased severity of CRS and a higher incidence of ocular complications, particularly among diabetic patients. IL-6 emerged as the most reliable indicator of disease activity. Monitoring these biomarkers in CRS patients can aid in early identification of high-risk individuals and guide timely therapeutic interventions to prevent vision-threatening complications. Keywords: Chronic rhinosinusitis, Diabetes mellitus, CRP, IL-6, TNF-α, Ocular complications, Inflammatory biomarkers.